Frequency-division multiplexing for multicomponent shearography - Bledowski, Ian A.; Charrett, Thomas O. H.; Francis, Daniel; James, Stephen W.; Tatam, Ralph P. (Osa Optical Society of America, 2013)
A new method of multiplexing the speckle patterns needed in multicomponent digital shearography systems is presented. Frequency-division multiplexing (FDM) of the measurement channels is achieved by recording speckle patterns from objects illuminated by intensity-modulated sources. Each source is modulated at a discrete frequency, which is less than half of the camera frame rate, and a bank of images of the modulated speckle patterns is captured. This allows for pixel-by-pixel Fourier-based extraction of the individual speckle patterns from peaks in the power spectra. The approach is demonstrated with a two-component in-plane shearography instrument.